Effects of massage with essential oils on bodily functionality in elite rifle shooting sport - Safronova, N. S.; Babushkina, O. F.; Fomenko, A. V.; Vikulova, N. N.; Agapov, D. V. (Theory and Practice of Physical Culture, 2018)
Objective of the study was to analyze benefits of massage with essential oils on bodily functionality in the elite rifle shooting sport. Elite junior (14-15 years old Class I athletes, n=19) and adult (20-29 year-olds qualified MS/ WCMS, n=8) rifle shooters were sampled for the study. The heart rate variability (HRV) test data were applied to split up the sample into four groups by the autonomic regulation and regulatory system functionality types. Junior group I (n=10, regulation type I) was subject to a rehabilitation massage course with application of essential (lavender, coriander, mint) oils followed by the HRV tests. The massage was found beneficial as verified by the functionality control improvements, mitigation of tension and moderate domination of the autonomic regulation of HRV. The study also classified the adult elite group with autonomic regulation type III with a moderate domination of the autonomic control.